Dependence on the Pyrimidine Biosynthetic Enzyme DHODH Is a Synthetic Lethal Vulnerability in Mutant KRAS-Driven Cancers. Issue 6 (21st June 2018) - Koundinya, Malvika; Sudhalter, Judith; Courjaud, Albane; Lionne, Bruno; Touyer, Gaetan; Bonnet, Luc; Menguy, Isabelle; Schreiber, Isabelle; Perrault, Christelle; Vougier, Stephanie; Benhamou, Brigitte; Zhang, Bailin; et al.
Summary: Activating KRAS mutations are major oncogenic drivers in multiple tumor types. Synthetic lethal screens have previously been used to identify targets critical for the survival of KRAS mutant cells, but their application to drug discovery has proven challenging, possibly due in part to a failure of monolayer cultures to model tumor biology. Here, we report the results of a high-throughput synthetic lethal screen for small molecules that selectively inhibit the growth of KRAS mutant cell lines in soft agar. Chemoproteomic profiling identifies the target of the most KRAS -selective chemical series as dihydroorotate dehydrogenase (DHODH). DHODH inhibition is shown to perturb multiple metabolic pathways. In vivo preclinical studies demonstrate strong antitumor activity upon DHODH inhibition in a pancreatic tumor xenograft model. Graphical Abstract: Highlights: DHODH inhibitors selectively inhibit the growth of KRAS mutant cell lines The inhibitors affect energy metabolism and glutamine levels in sensitive lines DHODH inhibitors synergize with some clinically used anticancer agents Abstract : Koundinya et al. show that inhibitors of the pyrimidine biosynthetic enzyme dihydroorotate dehydrogenase selectively inhibit the growth of KRAS mutant cell lines. Differential sensitivity of the mutant lines correlates with differential effects of the inhibitors on primary energy metabolism and glutamine levels, and the inhibitors synergize with some clinically used anticancer agents.